Islamic Accounting in Islamic Boarding Schools Based on ISAK 35 (Case Study of Darul Hasanah Islamic Boarding School in Galang) - Ritonga, Hanny Rahmadani; Siregar, Saparuddin; Marliyah, Marliyah (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2026)
Purpose: This research examines the implementation of Financial Accounting Standards Interpretation (ISAK) 35 in Darul Hasanah Islamic Boarding School, aiming to analyze the challenges in its adoption and provide strategic recommendations for improving the school’s accounting system. Design/Methodology/Approach: A qualitative case study approach was used, involving direct observations, in-depth interviews with financial managers and leadership, and document analysis. Data were analyzed using the Miles & Huberman method, which includes data reduction, presentation, and drawing conclusions. Findings: The study identifies key challenges in implementing ISAK 35, including human resource limitations in accounting, a lack of understanding of ISAK 35, and insufficient technological infrastructure. The study recommends a phased strategy for implementation, focusing on HR training, the use of digital-based accounting software, and the preparation of more systematic financial reports. Practical Implications: The findings suggest that adopting ISAK 35 can enhance financial transparency, strengthen trust from donors and the community, and ensure the sustainability of the boarding school’s operations. Originality/Value: This research contributes to the literature on nonprofit accounting by exploring the application of ISAK 35 in Islamic boarding schools and offering evidence-based recommendations for improving accounting practices in these institutions.